Cognitive functions in patients with locally advanced breast cancer during treatment and long-term posttreatment perio - T. N. Popova; Ye. A. Kuzevanova (Опухоли женской репродуктивной системы, 2014)
A retrospective analysis of the impact of chemotherapy on the cognitive functions of patients with locally advanced breast cancer during treatment and long-term posttreatment period revealed a direct correlation of the degree of cognitive dysfunctions in relation to the number of courses of chemotherapy and the time after its termination.